Lead enhances the phytotoxicity of Aegilops tauschii toward wheat seedlings - Wang, Ning; Huang, Zixuan; Shen, Xiaoxiao; Tian, Yaowu (Frontiers in Plant Science, 2025)
Heavy metal pollution in agricultural soil poses a significant threat to food security and the health of the ecosystem. This study investigated the allelopathic effects of Aegilops tauschii, a common weed found in wheat fields, on winter wheat (Triticum aestivum L. cv. ‘Zhengmai 132’) under lead (Pb) contamination. A completely randomized factorial design was used, employing a Petri dish filter paper bioassay with three concentrations of A. tauschii stem-and-leaf extract (0, 25 and 50 g/L) and three Pb levels (20, 80 and 160 mg/L), with five replicates per treatment combination. Low and high concentrations of A. tauschii extract, as well as low Pb levels, had little effect on wheat germination or seedling growth when applied alone. In contrast, medium and high Pb concentrations significantly inhibited these parameters in a dose-dependent manner. Combining the extract with Pb resulted in quantitative analysis using Colby’s method confirmed a significant synergistic inhibition, causing pronounced suppression of germination and early growth (P< 0.05). Physiological and biochemical analyses revealed a strong, synergistic oxidative stress response when the extract of A. tauschii interacted with Pb. Although antioxidant enzymes (SOD, POD and CAT) were activated in an attempt to counteract the oxidative stress, this increase was insufficient to prevent cellular damage. Consequently, the oxidative burst intensified, resulting in membrane injury and a 38.95% increase in thiobarbituric acid-reactive substances (TBARS) under the SCHPbH treatment. The interaction also disrupted hormonal homeostasis, decreasing the levels of the growth-promoting hormones gibberellin (GA3), indole-acetic acid (IAA) and zeatin riboside (ZR), while increasing abscisic acid (ABA). Under the strongest combined treatment (SCHPbH), GA3 decreased by 37.7%, and ABA increased by 40.6%, leading to a 74.6% reduction in the GA3/ABA ratio (P < 0.05). These alterations to growth-promoting and -inhibiting signals significantly lowered the GA3/ABA and IAA/ABA ratios. In summary, Pb contamination greatly increases the allelopathic effect of A. tauschii on wheat. The strongest combined treatment inhibited germination and growth by around 48%, indicating severe physiological disruption. These results emphasise the significant threat that this interaction poses to the stability of agroecosystems.